The 100 absolutely unbreakable laws of business success - Tracy, Brian (Berrett-Koehler, 2000)
Why are some people more successful in business? Why do some businesses flourish where others fail? In this text, the author draws on his experience to present set universal laws that lie behind the success of business people everywhere, in every kind of enterprise, large and small.